2020
DOI: 10.3390/ani10091481
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Moderate Exercise Program on Serum Markers of Bone Metabolism in Dogs

Abstract: The beneficial effect of physical activity on the musculoskeletal health in dogs is well recognized, but the level of intensity, duration, and frequency of exercise is not fully described. Measurement of serum markers of bone metabolism (bone alkaline phosphatase and osteocalcin as bone formation markers and C-terminal telopeptide as bone resorption marker) during four months of organized moderate-intensity physical training in Labrador retriever and Golden retriever dogs aged between 11.7–24.4 months, showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
1
8
1
Order By: Relevance
“…The onset of decline from baseline in the test group was later than the control group, which could be due to natural variability, environmental factors or higher mineral content of the test diet. BAP levels measured in the current study were higher than those previously reported [ 53 ], however this may be due to other factors such as activity level [ 54 , 55 ], which has been reported to be influential. CTx levels measured for both diet groups were within the normal range reported in dogs [ 56 , 57 ].…”
Section: Discussioncontrasting
confidence: 87%
“…The onset of decline from baseline in the test group was later than the control group, which could be due to natural variability, environmental factors or higher mineral content of the test diet. BAP levels measured in the current study were higher than those previously reported [ 53 ], however this may be due to other factors such as activity level [ 54 , 55 ], which has been reported to be influential. CTx levels measured for both diet groups were within the normal range reported in dogs [ 56 , 57 ].…”
Section: Discussioncontrasting
confidence: 87%
“…However, we failed to find that compared with conventional drug therapy, kinesitherapy has significant difference in improving biochemical markers of bone metabolism such as BGP, serum phosphorus, and serum calcium in POP patients, this may indicate that exercise therapy and conventional drug therapy have little difference in the impact of POP patients on biochemical markers of bone metabolism. This conclusion seems to be similar to previous animal experiments 49 , but at the same time we have also seen reports that exercise is helpful for bone metabolites 50 . Due to the limitation of the outcome indicators of the original study, the bone resorption markers recommended by the guidelines, such as serum C‐terminal telopeptide of type 1 collagen (CTX), were not reported in the original study, so analysis could not be performed.…”
Section: Discussionsupporting
confidence: 83%
“…In general, acute exercise was defined as lasting for up to 4 weeks [ 32 ], and chronic exercise was defined as that lasting for 8 weeks or longer [ 33 ]. Tables 3 [ 10 , 34 - 36 ] and 4 [ 37 - 39 ] show the changes in the physiological and hematological parameters according to acute and chronic exercise in dogs.…”
Section: Resultsmentioning
confidence: 99%
“…Vrbanac et al [ 39 ] analyzed biomarkers related to bone metabolism (bone alkaline phosphatase, c-telopeptide of type I collagen, osteocalcin) following low-intensity treadmill exercise three times a week, 25 min/time, for 16 weeks. They reported no differences in the levels of bone metabolism biomarkers.…”
Section: Resultsmentioning
confidence: 99%